PENERAPAN PENDEKATAN OPEN-ENDED DALAM MENINGKATKAN HASIL BELAJAR KETERAMPILAN BERBICARA - M. Zulham (Universitas Negeri Makassar, 2017)
Applying Open-Ended Approach in Improving Students’ Speaking Learning Outcomes. The objectives of this research are to find out the speaking learning outcomes. This study is an experimental research. The experimental unit in this research is the eighth grade students of SMP Negeri 1 Ponrang Selatan in academic year 2015/2016. In Selecting of experimental class, the researcher applies random sampling technique. The instrument of this study is a test of learning outcomes of pretest and posttest. The result of this research are: (1) speaking learning outcomes before applying open-ended approach is medium category; otherwise, speaking learning outcomes after applying open-ended approach is high category, (2) there is an improvement of students’ speaking learning outcomes after applying open-ended approach.